Threshold Levels of Poverty and Unemployment Rates on Economic Growth in Indonesia during COVID-19 Pandemic - Vita Kartika Sari; Malik Cahyadin; Aranka Ignasiak-Szulc; Riayati Ahmad (Universitas Negeri Malang, 2023)
During the COVID-19 pandemic, poverty and unemployment rates obstruct economic growth in Indonesia. Therefore, this study examines the threshold levels of poverty and unemployment rates on economic growth for 34 provinces in Indonesia in 2020 and 2021. Cross-section threshold regression is employed. Besides, the robustness check sets a non-linear cross-section regression. The findings reveal that threshold poverty rates in 2020 and 2021 were about 13.97% and 6.38%, respectively. At the same time, threshold unemployment rates were about 3.09% and 4.71%, respectively. Poverty and unemployment rates contributed significantly under U-shape in 2021 and 2020, respectively. The local government can emphasize lower poverty and unemployment rates to enhance economic growth in the long-term.